Spatialising happiness economics: Global metrics, urban politics, and embodied technologies. Issue 3 (23rd February 2022) - Pykett, Jessica
Abstract: Happiness has become a high‐profile goal for national governments, city authorities, and technology developers finding new ways to map and measure emotions through happiness economics, urban management, and digital emotion‐sensing. This paper advances critical geographical analysis of the neglected rationales, mechanisms, and implications of promoting the emotion of happiness. Researchers, policy‐makers, and publics alike are intrigued and troubled by how a growing concern with mapping and monitoring human happiness can co‐occur with increasing levels of social inequality, human suffering, anxiety, and sadness. The paper outlines the intersection between three key trajectories (economisation, spatialisation, and technologisation) in order to demonstrate how particular assumptions about space, time, scale, and subjectivity are implied in the framing of happiness as an objective scientific construct to be measured, and as a problem of government. These trajectories combine to create what I term a new spatial science of emotions, which is yet to be defined, empirically documented, and critically analysed. It considers what kind of economic futures and contested knowledge practices are laid out by this new spatial science of emotions. By bringing together insights from critical economic geographies of neuroscientific and behavioural forms of governance, geographies of well‐being, and social theories of embodied technologies, the paper challenges researchers to shift attention from subjective well‐being to public well‐being. Abstract : Happiness has become a high‐profile goal for national governments, city authorities and technology developers finding new ways to map and measure emotions through happiness economics, urban management and digital emotion sensing. This paper advances critical geographical analysis of the neglected rationales, mechanisms and implications of promoting the emotion of happiness. It challenges researchers to shift attention from subjective wellbeing to public wellbeing.